Learning PHP & MySQL, 2nd Edition - Davis, Michele; Phillips, Jon (O'Reilly Media, Inc., 2007)
PHP and MySQL are quickly becoming the de facto standard for rapid development of dynamic, database-driven web sites. This book is perfect for newcomers to programming as well as hobbyists who are intimidated by harder-to-follow books. With concepts explained in plain English, the new edition starts with the basics of the PHP language, and explains how to work with MySQL, the popular open source database. You then learn how to put the two together to generate dynamic content. If you come from a web design or graphics design background and know your way around HTML, Learning PHP & MySQL is the book you've been looking for. The content includes: PHP basics such as strings and arrays, and pattern matching A detailed discussion of the variances in different PHP versions MySQL data fundamentals like tables and statements Information on SQL data access for language A new chapter on XHTML Error handling, security, HTTP authentication, and more Learning PHP & MySQL explains everything from fundamental concepts to the nuts and bolts of performing specific tasks. As part of O'Reilly's bestselling Learning series, the book is an easy-to-use resource designed specifically for beginners. It's a launching pad for future learning, providing you with a solid foundation for more advanced development.